Calcifying Bowel Inflammation: A Case Report. (17th May 2010) - Klein, Jacques; Morel, Philippe; Toso, Christian
Abstract : We report about a previously healthy 72 year-old woman, presented with 6 days of left lower quadrant abdominal pain and constipation. There was no report of fever, melena, hematochezia or change in appetite. The physical exam demonstrated a distended abdomen with palpable left lower quadrant pain, without guarding. CT showed images compatible with a sigmoid diverticulitis and a calcification of the sigmoid colon. After antibiotic threatment, a colonoscopy was performed which revealed the presence of a shell in the sigmoid colon. Our case illustrates the need for a colonoscopy following an attack of diverticulitis to look for a cancer or rarely a foreign body.